Subjective Response to Alcohol and ADH Polymorphisms in a Select Sample of Young Adult Male East Indians and Africans in Trinidad and Tobago - Montane Jaime, Lazara Karelia (Rutgers University, 2014)
OBJECTIVE: Level of response to alcohol has been associated with risk of alcohol dependence in a number of ethnic groups. In the present study, subjective and objective responses to alcohol were evaluated in Indo-Trinidadians (Indo-T) and Afro-Trinidadians (Afro-T). Associations of alcohol dehydrogenase polymorphisms with response to alcohol, using the Subjective High Assessment Scale (SHAS), and breath alcohol concentrations (BrAC) were tested. METHOD: Regular male drinkers without alcohol dependence (n = 112) ages 18–25 years participated in alcohol challenge sessions consisting of placebo and two doses of alcohol (target BrAC: 0 g/dl for placebo, .04 g/dl low dose, and .08 g/dl high dose) and genotyped for variants in ADH1B*3 and ADH1C*2. RESULTS: Indo-T had significantly higher BrAC, pulse rates, and cortisol levels when compared with Afro-T but did not have significantly higher SHAS values. Higher responses on the SHAS items muddle/confused and nauseated were significantly associated with the presence of at least one ADH1B*3 allele following the high dose of alcohol in Afro-T. Indo-T with at least one ADH1C*2 allele displayed significantly different Drug × Time interactions for the SHAS item effects of alcohol at the low dose and for the SHAS items clumsy, muddle/confused, effects of alcohol, floating, drunk, and total at the high dose from Indo-T with two ADH1C*1 alleles. CONCLUSIONS: This is the first study that has investigated individual sensitivity to alcohol in a Caribbean population and in people of East Indian descent. Indo-T with at least one ADH1C*2 allele may be at higher risk for heavy drinking by feeling less of the effects of alcohol, including nausea. In Afro-T, having at least one ADH1B*3 allele appears to exert a protective effect by enhancing the unpleasant effects of alcohol, such as nausea and confusion.